Multifunctional Native Defects Boosting the Thermoelectric Transport in Few‐Layer PdPS - Zehao Yu; Meilin Li; Yu Yang; Peng Yu; Ady Suwardi; Lifa Zhang; Yunshan Zhao (Advanced Electronic Materials)
Abstract As a unique Cairo pentagonal 2D material, palladium phosphide sulfide (PdPS) has garnered immense interests due to its excellent optoelectronic properties, anisotropic electronic transport behavior, and good air‐stability. In addition, its puckered pentagon structure renders an ultralow thermal conductivity, making it a promising candidate for thermoelectrics applications. However, its thermoelectric transport has not been studied until now due to challenges in obtaining the atomic thin PdPS flake and further measurement. In this work, the thermoelectric performance of 2D PdPS is investigated. It is found that thermoelectric property of PdPS can be effectively manipulated via the delicate annealing treatment, which effectively regulate the defect concentrations. Remarkably, beyond regulating carrier concentrations and shifting the Fermi level closer to the conduction band, these defects also produce a large number of defect states. Consequently, ultra‐high power factor of 0.648 mW m−1 K−2 at room temperature is achieved, outperfoming other 2D materials reported to date. Furthermore, the anisotropic electronic transport properties of few‐layer PdPS are further studied and an extremely high electron anisotropic ratio of 47.37 are obtained at 20 K. The findings provide a new pathway for the development of nanoelectronic devices based on emerging 2D materials with high electronic anisotropy and thermoelectric performance.